Exploring the Effect of Compound Glycyrrhizin and Silybinin on the Metabolism of Pexidartinib in Rats Based on CYP3A4 and CYP2C9 - Yanding Su; Xinyi Wei; Qian Cheng; He Qi; Jianghui Chen; Xiang-Jun Qiu (Advances in Pharmacological and Pharmaceutical Sciences, 2023)
Pexidartinib offered a new therapeutic option for adult patients with symptomatic tenosynovial giant cell tumor (TGCT) who were refractory to surgical treatment and had severe morbidity or functional limitations. Meanwhile, the metabolism of pexidartinib was mainly mediated through the oxidation of cytochrome P450 (CYP) 3A and glucuronidation by uridine glucuronosyltransferase (UGT) 1A4 and attention shall be paid to CYP450-based drug-drug interactions during therapeutic dosing. This study aimed to examine the changes in the pharmacokinetics of pexidartinib by silymarin and compound glycyrrhizin on pexidartinib in vivo in rats by high-performance liquid chromatography (HPLC)-UV approach and to detect its expression in CYP3A4 and CYP2C9 using the western blot. The findings of chromatography experiments revealed that silybinin as well as compound glycyrrhizin increased the exposure of pexidartinib in rats and had a significant inhibitory effect on the metabolism of pexidartinib. The results of immunoblotting assays suggested that silybinin as well as compound glycyrrhizin inhibited the protein expression of CYP3A4 and CYP2C9 in rats. Therefore, the combination of pexidartinib with silybinin and compound glycyrrhizin should be monitored to avoid clinical adverse effects.